INCLUSIVE EDUCATION IN INDONESIA: POLICY ANALYSIS, CHALLENGES, AND HIGH- QUALITY IMPLEMENTATION EFFORTS TOWARDS ACHIEVING ACCESS ANDEDUCATIONAL EQUALITY FOR ALL STUDENTS WITH SPECIAL NEEDS - Siminto; Komari Komari; Fenni Kurniawati Ardah; M. Ali Mauludin; Teguh Pribadi (Adisam Publisher, 2023)
In inclusive education, Indonesia stands at a pivotal juncture, striving to balance policy aspirations with on-the-ground realities. This research, encapsulated in the paper